Import Growth and the Impact on the Florida Strawberry Industry - Zhengfei Guan; Dong Hee Suh; Hayk Khachatryan; Feng Wu (EDIS)
The United States is the second largest producer of strawberries after China, and Florida, along with California, accounts for about 98% of the total US production. In recent years, the US strawberry industry has become increasingly concerned with competition from Mexico. This 3-page fact sheet written by Zhengfei Guan, Dong Hee Suy, Hayk Khachatryan, and Feng Wu and published by the UF/IFAS Food and Resource Economics Department describes the impact of imported strawberries on the Florida strawberry industry and explains how the industry can adapt to meet the challenge. http://edis.ifas.ufl.edu/fe1022